Therapist-Reported Differences between Teletherapy via Phone and via Videoconferencing - Vera Békés; Cédric Gill Ménard; Natale Schmitz; Katie Aafjes-van Doorn (Brain Sciences, 2023)
When therapists provide teletherapy they can choose between teletherapy via phone and teletherapy via videoconferencing, however, little is known about differences between using these two teletherapy formats. We aimed to compare therapists’ attitudes, level of professional self-doubt, and experience of the therapeutic relationship in sessions conducted via phone versus via videoconferencing. We administered an online survey to 117 therapists who had experience with sessions both via phone and videoconferencing. The results suggested that therapists’ attitudes and perceptions of the therapeutic relationship were similar. However, therapists’ level of professional self-doubt was higher in sessions conducted via videoconferencing. Therapists with previous experience of conducting teletherapy via phone perceived phone sessions more positively. Thus, familiarity with videoconferencing technology might be more important in shaping therapists’ attitudes and confidence than the type of technology per se. This highlights the importance of practicing with new technologies.